Student Guidance In Identifying Student Learning Characteristics Based On The Speed Of Understanding Mathematical Material - Puspitasari, Yesi; Sari, Winda Purnama; Lailiyah, Nurul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This community service aims to analyze student learning characteristics based on the speed of understanding mathematics material through observation of the learning process and analysis of daily test scores in class VIII-B students of SMP Negeri 1 Kapongan. The results of the observation showed a quite striking difference in ability, where only a few students were active, confident, and able to answer questions quickly, while most other students appeared passive, hesitant, lacked focus, and showed low learning motivation. Analysis of daily test scores supported the findings of the community service, the results of which 60% of students were in the low category (0–59), 28% in the medium category (60–69), 8% in the high category (70–89), and only 4% reached the very high category (90–100). This distribution of scores indicates that the majority of students have not yet understood the material well. This finding confirms that the factors of activeness, attention, motivation, and self-confidence have a strong influence on the speed of student understanding. This community service activity also provides an important overview for teachers and prospective educators to use more varied learning strategies that are appropriate to the learning characteristics of each student.